2-AG and anandamide enhance hippocampal long-term potentiation via suppression of inhibition - Lemtiri-Chlieh, Fouad; Levine, Eric S. (Frontiers in Cellular Neuroscience, 2022)
It is widely accepted that exogenous cannabinoids can impair short-term memory and cognition in humans and other animals. This is likely related to the inhibition of long-term potentiation (LTP), a form of synaptic plasticity, by the global and sustained activation of CB1 cannabinoid receptors in the presence of exogenous agonists. Conversely, the temporally and spatially restricted release of endogenous cannabinoid (eCB) ligands may enhance synaptic plasticity in a synapse-specific manner. We examined the role of eCB signaling in LTP by recording field excitatory postsynaptic potentials (fEPSPs) in the CA1 stratum radiatum in hippocampal slices from juvenile mice. LTP was induced either electrically, by theta burst stimulation (TBS), or pharmacologically, by treatment for 15 min with a solution designed to increase intracellular cAMP (chem-LTP). A stable and long-lasting potentiation in fEPSP slope following TBS was significantly reduced by blocking cannabinoid receptor activation with CB1 receptor antagonists. Chem-LTP caused a sustained 2-fold increase in fEPSP slope and was also blocked by CB1 receptor antagonists. TBS-LTP was partially reduced by inhibiting the synthesis of the endogenous ligands 2-AG and anandamide. A similar effect was observed with chem-LTP. Blocking inhibitory synapses completely prevented the effect of CB1 receptor antagonists or inhibition of eCB synthesis on TBS-LTP and chem-LTP. These results indicate that simultaneous activation of CB1 receptors by 2-AG and anandamide enhances TBS-induced and pharmacologically-induced LTP, and this effect is mediated by the suppression of inhibition at GABAergic synapses.